A középkori Magyarország regionális tagolódása - Csüllög, Gábor (Közép-Európai Közlemények, 2009)
The Hungarian Kingdom is not a conglomerate of provinces belonging to the natural sites of the Carpathian basin, and is not a rigid and simple structure organized around a central region, but appears to be an interrelated active site – pro-site – back-site system, organized as a region to the areal organization lines by regional processes. The organization of the interrelated regional factors (active areal sites, areal states, center sites, pro-sites, back-sites, flow paths) within the larger area form areal units of similar structure and operation, but of different character in organizational direction and in certain energies (preceding areal structure, external centers, external boundaries). These areal units can be interpreted as geographic regions. The organization of pro-sites and back-sites, with various area utilization rates, to center sites represent the model of geographic division of labor in the Carpathian basin.